2020
DOI: 10.1007/s10461-020-02843-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Mistrust (or HIV Conspiracy Theories) and Willingness to Use PrEP Among Black Women in the United States

Abstract: Uptake of pre-exposure prophylaxis (PrEP) among Black women living in the US is suboptimal. We sought to determine the association between HIV conspiracy beliefs (HIV-related medical mistrust) and willingness to use PrEP among Black women. We analyzed data from the 2016 National Survey on HIV in the Black Community (NSHBC), a nationally representative crosssectional survey. Among NSHBC participants, 522 were women and 347(66.5%) reported expanded PrEP indications. Only 14.1% were aware that PrEP exists; 30.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…However, some research has shown that endorsing conspiracy theories can have some positive consequences, as it allows individuals to question social hierarchies and, as a result, encourage governments to be more transparent ( Clarke, 2002 ; Fenster, 1999 ; Swami & Coles, 2010 ). In a medical context, there is some evidence that belief in HIV-related conspiracy theories is significantly positively associated with HIV-testing ( Ford, Wallace, Newman, Lee, & Cunningham, 2013 ) and with the willingness to use pre-exposure prophylaxis ( Ojikutu et al, 2020 ). We argue that a better understanding of when and why conspiracy theories have different consequences requires focusing on the content of an endorsed conspiracy theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, some research has shown that endorsing conspiracy theories can have some positive consequences, as it allows individuals to question social hierarchies and, as a result, encourage governments to be more transparent ( Clarke, 2002 ; Fenster, 1999 ; Swami & Coles, 2010 ). In a medical context, there is some evidence that belief in HIV-related conspiracy theories is significantly positively associated with HIV-testing ( Ford, Wallace, Newman, Lee, & Cunningham, 2013 ) and with the willingness to use pre-exposure prophylaxis ( Ojikutu et al, 2020 ). We argue that a better understanding of when and why conspiracy theories have different consequences requires focusing on the content of an endorsed conspiracy theory.…”
Section: Introductionmentioning
confidence: 99%
“…Trying to deal with this scenario requires developing new forms of coping, as many forms of personal contact became unfeasible during the pandemic, such as group activities, parties, gym and family contact. This context increases the uncertainties about the future and safety of the population, especially for LGBTQIA2+ [ 39 , 40 ], historically more affected by lack of social support, inequalities and difficulties in accessing the health services. It is believed that these practices can represent an escape valve from the harmful social effects of the pandemic, modulated by individual behaviors, not exclusive to Brazilian or Portuguese MSM, but at the global level [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an unexpected scenario, in which their usual social supports (family and friends) have limited, and sometimes precluded contact, the search for a routine health monitoring is in a second place, but does not hinder the search for sexual experiences. In a risk compensation logic [ 40 , 41 ], the already known barriers to accessing health services (fear, stigma, and welcoming) are added to the risk of being exposed to COVID-19, in contrast to the pleasure and release offered by sex in a stressful situation. It is important to point out that failure to comply with the social distancing measures does not exempt MSM from the concern about at-risk exposure to HIV infection, since the behavior is an attempt to reduce the deleterious effects of the pandemic [ 18 , 23 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 There are numerous barriers to PrEP use among Black women, including underestimation of risk by healthcare providers, lack of access to providers who prescribe PrEP, medical mistrust, and healthcare providers who have racial or other biases that negatively impact clinical decision making. 29…”
Section: Access For All Womenmentioning
confidence: 99%